EFEKTIVITAS SUHU TERHADAP KELANGSUNGAN HIDUP KERANG ABALONE Haliotis squamata - Putra Basir, Aditya; Abidin, Jenny; Sanipan, Devita (Jurnal Borneo Saintek, 2023)
Abalone (Haliotis squamata) is a species of mollusk that has important economic value. The high market demand causes an increase in the level of exploitation in nature. Therefore, abalone cultivation activities in controlled containers must be carried out to meet market demand and prevent over-exploitation in nature. One of the parameters that must be considered for the success of abalone cultivation is temperature. This study aims to determine the effect of different temperatures on the survival rate of abalone shellfish. This study used a completely randomized design with 3 treatments, A (temperature 24 oC), B (temperature 27 oC), C (temperature 30 oC) and temperature 29 oC as a control. The parameters measured were the survival and weight growth of abalone mussels. The results showed that the highest survival rate was in treatment A with a value of 70% and B with a value of 50%. The lowest survival rate was in treatment C with a value of 40% while the weight growth of abalone mussels in treatment A increased more with the growth value of abalone weight 8.91 gr. Based on the results of the analysis of variance ANOVA showed that the temperature difference treatment had a significant effect on the survival of abalone shells where F count 2.126 F table 0.219 and the results of calculating the weight of abalone shells that were kept at different temperature media obtained F count 3.385 F table 0.140, which means there was a significant difference in the survival and growth of abalone shell weights.